Use of hyperattenuated poliovirus as a replacement for Sabin or wild-type strains for laboratory assays in a post eradication world. Issue Volume 1(2019)Issue A (8th March 2019) - Fox, Helen; Carlyle, Sarah; Minor, Philip; Macadam, Andrew
Abstract : Poliovirus serotype 2 (PV2) has been declared eradicated and was removed from the live vaccine programme in 2016. WHO have developed the Global Action Plan (GAPIII) to describe containment conditions for laboratory work with poliovirus after eradication, and in the UK, all PV2 has been reclassified to hazard group 3 (HG3). Laboratory work involving live poliovirus will continue to be required years after eradication for the purposes of: vaccine testing; environmental surveillance; immunoglobulin testing; and for the development of new public health interventions. Compliance with GAPIII and HG3 containment conditions would impose financial burden and failure would lead to disruption to essential activities. Development of safer poliovirus strains for use outside of containment could overcome these issues. The S19 poliovirus strain, designed to be hyperattenuated and extremely genetically stable, was used as a cassette for the introduction of capsid proteins of other strains and serotypes (Knowlson et al. 2015), originally for vaccine production. S19 viruses are unable to infect transgenic mice (by intraspinal inoculation) or non-human primates (by mouth) at very high doses and are unlikely to infect humans at biological temperature. PV2 S19 strains have recently been approved for use outside of GAPIII containment requirements by the Containment Advisory Group. Validation of strains for laboratory assays and a highly sensitive QC assay based on NGS will be described.